Professor Julius F. Leo – Scientist, Municipal Manager, Politician, and His Economic and Political Views - Pociecha, Józef (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The subject of the paper is the representation of the life and work of Julius F. Leo, his achievements and scientific opinions in the area of public finance, merits in the field of municipal administration as well as his views and political career. J. F. Leo was one of the outstanding personalities of Cracow in the early 20th century. He was the first President of the Polish Statistical Association founded in Cracow in 1912. He was a prominent lawyer and economist of his time, he worked on problems of public finances as a Professor of tax law and treasury sciences at the Jagiellonian University. During his studies and trips abroad he became acquainted with the issues of economic statistics, the validity of which, he had a great understanding for. A large part of his public activity was associated with the activities of the municipality. Since 1893 he was a councilor of Cracow, in 1901 he became the Vice‑Mayor and then in 1904 (until his death) the Mayor of Cracow. During his time in office he introduced a number of important reforms in the management of the city. J. F. Leo’s life’s work was a significant widening of the city limits, hence he was named “the father of the great Cracow”. Julius F. Leo was an important politician, the leader of the Galician neo‑conservatives. In 1901 he was elected to the Galician Sejm and in the year of 1904 to the Austrian Parliament. His political views have evolved from conservatism to liberalism. In 1912 he became the President of the Polish Circle in the Austrian Parliament. At the outbreak of the First World War he supported creation of Polish Legions by Józef Piłsudski. He was also the head of the Supreme National Committee. However, he did not live long enough to experience the moment of Poland regaining its independence, he died in February 1918.